Structure and Decay Properties of Th Isotopes Using E-RMFT Formalism - M. Das; K. C. Naik; N. Biswal; R. N. Panda (Atom Indonesia, 2022)
In the present scenario, the search for the thermally fissile nuclei is crucial and also important not only for the research background of nuclear physics but also for the great social and economic impact on the country. Many theoretical works have been performed to analyze a series of Th and U-isotopes and found that some of these isotopes are stable against α-decays and spontaneous fission. Here, we have chosen the isotopic chain of Th-nuclei for the present analysis using relativistic mean-field formalism. The work also explores a few stable isotopes in this region of the nuclear landscape, which is crucial for understanding the exotic region of the nuclear landscape. The objective of this work is to study the bulk properties such as binding energies, root mean square charge radii, neutron-proton radii, neutron skin-thickness as well as intrinsic properties such as excitation energy and specific heat for the 216-238Th-isotopic chain. Furthermore, the stability of these isotopes is investigated through their possible decay chain analysis. The relativistic mean-field theory was used to obtain the nuclear bulk properties, namely, binding energies, root-mean-square charge radii, neutron skin-thickness, and excitation energy. The steady solution of the temperature-dependent effective relativistic mean-field equations was obtained self-consistently by taking different inputs of the initial deformations. All the calculations were done for NL3, FSUGarnet and IOPB-I parameter sets for 216-238Th-isotopes. The decay energy of α (Qα) and β-decay (Qβ) were calculated from the binding energies and were further used to obtain the corresponding half-lives. We have analyzed the structural and decay properties of 216-238Th isotopes. The excitation energy and specific heat are also estimated for these considered nuclei by using the temperature-dependent effective relativistic mean-field (E-RMFT) formalism for NL3, FSUGarnet and IOPB-I parameters sets. The calculated results are compared with the available experimental data and found similar observations for all the parameter sets at a given temperature. The excitation energy study signifies the shell melting point where maybe the shape transition occurs. Three phenomenological formulae such as Viola-Seaborg, Royer and modified universal decay law are adopted for the calculation of α-decay half-lives. We found lower values of α-decay half-lives indicating a higher rate of β-decay for the isotopic chain.